A bibliometric analysis of emerging research directions in food science and technology based on the Dimensions Database (2014–2024) - Iriawan, Gabriella; Miah, Lie; Prabowo, Norbertus Krisnu (Berkala Ilmu Perpustakaan dan Informasi, 2025)
Introduction. This bibliometric study examines publication trends in food science and technology between 2014 and 2024, providing insights into emerging research directions, thematic gaps, and academic productivity. Data Collection Methods. We used the metadata from the Dimensions database identified 9,265 articles, of which 5,650 were selected using the PRISMA protocol. Data Analysis. Statistical analyses were performed using Microsoft Excel and Google Sheets, while VOSviewer was employed to visualize prolific authors, international collaborations, and keyword clusters. Results and Discussion. The publication trend conformed to a polynomial regression model, reaching its peak in 2021. The United States emerged as the most productive contributor country. Four principal interdisciplinary themes have emerged: food chemistry, industrial practices, administration, and social implications. Technologies such as artificial intelligence (AI) and the Internet of Things (IoT) have been shown to enhance agricultural efficiency, food safety, and personalized nutrition, aligning with Industry 4.0 initiatives aimed at sustainable food systems. Conclusion. The findings indicate a future trajectory propelled by technological innovation, especially in fields such as nanotechnology, foodomics, biosensors, and metabolomics. Prominent keywords including AI, IoT, spectroscopy, and chemometrics reflect a move toward increased automation and digitalization within food science and technology.